INTERTEXTUAL STUDY OF FEMINISM ELEMENTS ON THE NOVEL DIARY SANG KEMBANG MALAM BY AGUNG WEBE AND NOVEL CATATAN SANG MODEL BY NOVANKA RAJA - T. Takwa; Kiki Nuliana Ningsih (Universitas Sembilanbelas November Kolaka, 2018)
Intertextual theory considers that none of the literary works are truly independent without any influence from other literary works. The same is true of literary works in this study. This study aims to describe the intertextual study of the feminist elements of the novel Sang Kembang Malam by Agung Webe and the novel Catatan Sang Model by Novanka Raja. The research of the two novels focused on intertextual studies of elements of feminism. The method used in this study is a qualitative descriptive method. The data collection technique used in the form of a reading-recording technique. Data analysis techniques used content review techniques and analyze structures in both novels that focus on the facts of the story. The results show, (1) the intertextual relationship in the division of labor and economic system in the novel Diary Sang Kembang Malam by Agung Webe and the novel Catatan Sang Model karya Novanka Raja, namely (a) Gita representing Fatia, (b) Non-established Gita representing with Fatia not well established, (c) Jupri representing with Fatia's father, (d) Jupri a fraudster, blackmailer, and oppressor representing Fatia's oppressive father, (e) Jupri who was not well-established representing the established Fatia's father, (f) PSK representing with the model, (2) intertextual relations in the education and governance system in the novel Sang Kembang Malam by Agung Webe and the novel Catatan Sang Model karya Novanka Raja, namely (a) Gita who dropped out of school representing Fatia who was able to finish her education well ( b) Gita who was successful as a prostitute representing Fatia who was successful as a model, (c) Nita representing with Mrs. Fatia as a supporter of professional success, (d) Mr. Semar representing with Fatia's father as a successor tuned various problems they faced in carrying out their profession, (e) Gita representing Fatia in terms of having the right to choose to determine the future and find her identity, (3) Intertextual relationships in the nature of gender identity and the relationship between sexuality and biological reproduction in the novel Diary Sang Kembang Malam by Agung Webe and the novel Catatan Sang Model karya Novanka Raja, namely (a) Gita representing with Fatia suffered the same fate about sexual treatment, (b) Jupri representing with Person 1 as the perpetrator of abuse, (c) Mr. James representing with Male 1 as the perpetrator of harassment, (e) Gita experience sexual harassment physically representing with Fatia who is physically and non-physically sexually abused.